Coloration Mechanism of Fe Ions in β-Quartz s.s. Glass-Ceramics with TiO2 and ZrO2 as Nucleation Agents - Nakane, Shingo; Kawamoto, Kosuke (Frontiers in Materials, 2017)
Transparent Li2O-Al2O3-SiO2 low-expansion glass-ceramics have an undesirable brown color owing to Fe ions as a contaminant, whereas the mother glass normally has a clear appearance. Elucidation of the coloration mechanism during crystallization is important for industry to develop highly transparent materials. In this study, the mother glass contained SiO2, Al2O3, and Li2O as its principal constituents and TiO2 and ZrO2 as nucleation agents. The amount of contaminant Fe ions in the form of Fe2O3 was 0.03 wt%. It was confirmed that the coloration was appeared by the coexistence of Fe and Ti ions in the glass matrix based on the experimental results using Ti-containing and Ti-free glasses with a composition identical to that of the glass matrix. The coordination and oxidation state of the Fe ions were not changed by the coexistence of Ti ion according to the results of XANES measurement. The coloration is considered to be due to the formation of Fe-O-Ti by the concentration of Fe and Ti ions in the glass matrix phase during the crystallization process.